Assessment of the tumourigenic and metastatic properties of SK-MEL28 melanoma cells surviving electrochemotherapy with bleomycin - Todorović, Vesna (Radiology and oncology (Ljubljana), 2012)
Background. Electrochemotherapy is a local treatment combining chemotherapy and electroporation and is highly effective treatment approach for subcutaneous tumours of various histologies. Contrary to surgery and radiation, the effect of electrochemotherapy on metastatic potential of tumour cells has not been extensively studied. The aim of the study was to evaluate the effect of electrochemotherapy with bleomycin on the metastatic potential of human melanoma cells in vitro. Materials and methods. Viable cells 48 hours after electrochemotherapy were tested for their ability to migrate and invade through Matrigel coated porous membrane. In addition, microarray analysis and quantitative Real-Time PCR were used to detect changes in gene expression after electrochemotherapy. Results. Cell migration and invasion were not changed in melanoma cells surviving electrochemotherapy.Interestingly, only a low number of tumourigenesis related genes was differentially expressed after electrochemotherapy. Conclusions. Our data suggest that metastatic potential of human melanoma cells is not affected by electrochemotherapy with bleomycin, confirming safe role of electrochemotherapy in the clinics.
Keywords: bleomicin; Bleomycin; Cell survival; Drug therapy; Electroporation; elektrokemoterapija; melanom; Melanoma; Oligonucleotide array sequence analysis; Polymerase chain reaction; Tumor cells, cultured; tumorne celice